DANCE, DON’T DRIVE: RESILIENT THINKING FOR TURBULENT TIMES (Utah Environmental Law Review, 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Shedding a way of life based on limitless growth, the celebration and reward of excess, along with deeply ingrained habits of acquisition, consumption, and waste is going to be an overwhelming challenge. The culture of ‘faster-bigger-more' will not yield easily to a new orientation where sustainability is the rule. We are going to need all the expertise we can muster to understand how we have overloaded the carrying capacity of our planet and its ecosystems-and how we can tread from here on with a lighter footprint. Innovations in technology, policy, law, and practices are absolutely essential. We need new models. Integrating our concerns for the health of ecosystems and the vitality of the individuals and human communities that inhabit those ecosystems is crucial. As we move forward, we must learn not just to connect, but to weave. It is crucial that we change the goals and rules we live by through new laws, policies, programs, incentives, and constraints. At a deeper level, I believe that living within the boundaries of Nature requires a profound shift in perspective. We need to stop seeing Nature merely as a limitless source of lifeless commodities to be used and traded and start seeing the natural realm as an astounding web of living communities that includes us. And we need to see that we do not live above and beyond the dynamic of the earth's operating systems that sustain life itself. After centuries of driving economies , we must learn to dance with ecosystems .